Financial effect of remittances - Dana Luiza GRIGORESCU (Theoretical and Applied Economics, 2024)

(untitled)
Remittances are those amounts obtained outside the country’s borders by economic immigrants in the first place. Remittances are a germ factor of economic migration. The assumptions of the statistical-econometric models used in migration analysis give a complete picture of the degree and complexity of migration in each country. Also, in these models that are described in detail in the article, the correlation that exists between emigration and remittances is highlighted. Of course, remittances as we know have an impact on economic growth in each country, but in order to reach clear conclusions on the basis of which national and international programs in this field can be planned, we must use methods, statistical-econometric models of analysis in the first turn of migration. Thus, it is about the neoclassical model that approaches the essence and reasons of migration at the macroeconomic level. On the other hand, there is also a neoclassical model that follows the microeconomic approach. This model represents a deepening of the neoclassical macroeconomic model. At the macroeconomic level, the analysis of remittances must be based on the volume of periodic transfers from the migrant to the family or other groups in the country in order to identify the effectiveness of these transfers, in order to be able to study the effect of migration on the income level of the population, but also on economic growth.